The effect of fintech on the user’s trust, satisfaction, and continuance intention in Islamic banks – the perspective of a developing country - Aidarus, Fathi; Abu, Abdullahi (Journal of Asian Scientific Research, 2025)
Fintech, which involves the use of new technology in delivering financial services, enhances customer satisfaction, results in better customer retention, and fosters business growth. This study aims to investigate the effect of Fintech on customer trust, satisfaction, and continuance intention. A comprehensive questionnaire was administered, and data were collected from a sample of 113 customers of Islamic banks in a developing country. As a case study, Somalia was selected due to its rapid growth in the use of Fintech and the limited research conducted on the subject. A PLS-SEM was utilized to analyze the primary data collected and test the hypothesized associations. The results of the study show that the user’s trust in Fintech services is significantly influenced by perceived ease of use and service quality, but not by perceived usefulness. Trust also has a significant positive effect on customer satisfaction. Moreover, we found that the continuance intention is significantly and positively affected by trust and customer satisfaction. The study makes a valuable contribution to the literature on Fintech while shedding light on the use of Fintech in the Somali context. Furthermore, the study provides valuable insights to regulators, policymakers, the academic community, and Islamic bank stakeholders.